Simultaneous measurement of the ratio R = B(t -> Wb)/B(t -> Wq) and the top-quark pair production cross section with the D0 detector at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Mendoza, L.; et al. (Amer Physical Soc, 2008)
We present the first simultaneous measurement of the ratio of branching fractions, R = B(t --> Wb)/B(t --> Wq), with q being a d, s, or b quark, and the top-quark pair production cross section sigma(t (t) over bar) in the lepton plus jets channel using 0.9 fb(-1) of p (p) over bar collision data at root s = 1.96 TeV collected with the D0 detector. We extract R and sigma(t (t) over bar) by analyzing samples of events with 0, 1, and >= 2 identified b jets. We measure R = 0.97(-0.08)(+0.09) (stat + syst) and sigma(t (t) over bar) = 8.18(-0.84)(+0.90) (stat + syst) +/- 0.50(lumi) pb, in agreement with the standard model prediction.